Kounis syndrome following multiple wasp stings: A case report. Issue 3 (14th March 2023) - Basnet, Angela; Khadka, Manoj; Alismail, Abdullah; Shrestha, Dhan Bahadur; Thapa, Ashok
Abstract: This is a case of Kounis syndrome with chest tightness, lightheadedness, unconsciousness, and features of shock following multiple wasp stings. Despite cardiopulmonary resuscitation and management of allergic and cardiac symptoms, the patient died. Kounis syndrome should be suspected when a patient presents with allergic symptoms and acute coronary syndrome.